Spiritual formation and the nurturing of creative spirituality A case study in Proverbs - Viljoen, Anneke (2016)
The article is positioned in the interface between Old Testament scholarship and the discipline of spiritual direction of which spiritual formation is a component. The contribution that a Ricoeurian hermeneutic may make in unlocking the potential which an imaginal engagement with the book of Proverbs may hold for the discipline of spiritual formation was explored. Specifically three aspects of the text of Proverbs illustrated the creative process at work in the text, and how it converges with the concept of spiritual formation and the nurturing of creative spirituality. These aspects were, the development in Lady Wisdom's discourses, the functional definition of the fear of Yahweh (illustrated from Proverbs 10:1-15:33), and the paradigmatic character of the book of Proverbs.Intradisciplinary and/or interdisciplinary implications: The research is positioned in the interface between Old Testament studies and Practical Theology. The research results in the enhancement of the interdisciplinary dialogue and interchange of resources between the named disciplines with regard to the interest in formation of persons that the biblical book of Proverbs and the discipline of spiritual formation shares.Keywords: Spiritual formation; fear of Yahweh; Proverbs; Wisdom; Hermeneutics; Paul Ricoeur; Symbolic world; Textual reference
Keywords: Hermeneutics; Paul Ricoeur; Proverbs; Spiritual Formation; Symbolic world; Textual reference; Wisdom; fear of Yahweh